NEW METHOD FOR ESTIMATION OF MULTI-HARMONIC POWER SIGNAL PARAMETERS - Petrovic, Predrag (Journal on Processing and Energy in Agriculture, 2021)
A systematic analytical procedure for simultaneous estimation of the fundamental frequency, the amplitudes and phases of harmonic waves was proposed in this paper. In order to reduce complexity in the calculation of unknown parameters, a completely new reduced analytical expression is derived, which enabled fast and precise estimation with a small numerical error. Individual sinusoidal components stand out from the input complex-harmonic signal with the filter with a finite-impulse response (FIR) comb filters. The algorithm that is proposed in the operation is based on the application of partial derivate of the processed and filtered input signal, after which it is performed weighted estimation procedure to better estimate the values size of the fundamental frequency, amplitude and the multi-sinusoid signal phase. The proposed algorithm can be used in the signal reconstruction and estimation procedures, spectral processing, in procedures for the identification of the system that is observed, as well as other important signal processing areas. Through the simulation check, the effectiveness of the proposed algorithm was assessed, which confirmed its high performance.